2022
DOI: 10.1371/journal.pone.0274945
|View full text |Cite
|
Sign up to set email alerts
|

Freezing stress affects the efficacy of clodinafop-propargyl and 2,4-D plus MCPA on wild oat (Avena ludoviciana Durieu) and turnipweed [Rapistrum rugosum (L.) All.] in wheat (Triticum aestivum L.)

Abstract: The occurrence of freezing stress around herbicides application is one of the most important factors influencing their performance. This experiment was performed to evaluate the efficacy of clodinafop-propargyl and 2,4-D plus MCPA (2,4-Dichlorophenoxyacetic acid plus 2-methyl-4-chlorophenoxyacetic acid), the most important herbicides used in wheat fields in Iran, under the influence of a freezing treatment (-4°C). Wheat and its two common weeds, winter wild oat (Avena ludoviciana Durieu) and turnipweed [Rapist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Therefore, it is clear that the high density of this species during autumn and spring is attributed to its ability to effectively respond to a wide range of temperatures in these two regions. Relatively high optimal temperatures for maximum germination of this species indicate that conditions for increased germination and growth are likely to be provided due to the extreme climate change in Iran and the rising temperatures during cold seasons (Hasanfard et al 2022). Eslami (2011) reported that the highest germination percentage for populations of lambsquarters ( Chenopodium album L.) from Iran occurred at 25/15 C, while for populations from Denmark, it occurred at 20/10 C.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is clear that the high density of this species during autumn and spring is attributed to its ability to effectively respond to a wide range of temperatures in these two regions. Relatively high optimal temperatures for maximum germination of this species indicate that conditions for increased germination and growth are likely to be provided due to the extreme climate change in Iran and the rising temperatures during cold seasons (Hasanfard et al 2022). Eslami (2011) reported that the highest germination percentage for populations of lambsquarters ( Chenopodium album L.) from Iran occurred at 25/15 C, while for populations from Denmark, it occurred at 20/10 C.…”
Section: Resultsmentioning
confidence: 99%